Implementasi Konsep ESD Plus Dalam Mata Kuliah Pengembangan Kepribadian (MPK) Melalui Model Training Kader Bangsa Mahasiswa - Heri Santoso; Arqom Kuswanjono; Surono Surono (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2016)
This community service activities was designed to (1) give a critical evaluation of the concept and implementation of Education for Sustainable Development (ESD) and Courses on Character Development (Mata Kuliah Pengembangan Kepribadian/MPK) at universities in contemporary Indonesia and (2) to design an appropriate model of implementation of ESD concept for improving the quality of MPK program. The methods on this study are literature studies, workshop on instrument design, Focus Group Discussion (FGD), implementation of ESD concept in co-curricular activities, and evaluation. The program will be held in Center for Pancasila Studies (PSP-UGM), at Taman Makam Pahlawan Kusumanegara, Pakem Orphanage center, and scavengers community in Condongcatur. The expected results of the program are (1) a critical note on the concept and implementation of ESD and MPK at universities in Indonesia and (2) a model and module of implementation of ESD PLUS through Training Kader Bangsa (TKB) which are more adaptable and appropriate with the local genius of Indonesia.